Hospitalidade e competitividade em unidades de conservação: estudo de casos múltiplos na rota das emoções - RIBEIRO, Ruan Tavares (2017)
Protected areas have more and more influenced the demand of tourists to a particular region. There are studies concerning the engagement of protected areas with stakeholders that influence, may influence or may be influenced by tourist activities practiced in these areas. The objective of this master’s thesis is to analyse hospitality relations between the protected areas management and its stakeholders related to tourism, focusing on their influence for the competitiveness of destinations. The study objects are three protected areas that belong to a route called “Rota das Emoções”, located in the northeast region of Brazil: National Park of Lençóis Maranhenses, National Park of Jericoacoara and Delta do Parnaíba Environmental Protection Area. A multiple-case study was developed through qualitative and quantitative methods: semi-structured interviews, websites analysis, unsystematic observation, and survey. Data were collected and organized from categorization previously elaborated, and analysed through Content Analysis. It was verified that not all tourist services offered by stakeholders, such as hotels, are influenced by relationships established with the management (the host) of national parks and environmental protected areas. However, other stakeholders, such as tour guides and travel agencies, depend on a certain relation with the host concerning the need to respect rules for their acreditation. Hospitality relations betwen the host and its stakeholders related to tourism favour mutual trust by influencing directly both management conditions of the protected areas and competitiveness of the destinations where they are located. The results also showed that hospitality relations affect positively visitors’ return intention.